ANALISIS PENDIDIKAN KARAKTER PADA KURIKULUM MERDEKA DALAM MATA PELAJARAN IPAS DI SEKOLAH DASAR - Jadidah, Ines Tasya; Rahmasari, Fani; Dewi, Windy Anisa; Mutmainnah, Ayu (Jurnal Ilmu Pendidikan Muhammadiyah Kramat Jati, 2024)
Character education is an effort to shape the personality of students in accordance with values, morals, and ethics. This effort can be realized through the delivery of materials, exemplary behavior, and other learning strategies to achieve planned learning objectives. Thus, character education becomes one of the most important aspects of education, as it is not only about intellectual development, skill enhancement, but also about cultivating good attitudes. This research aims to analyze the meaning of character education in the "Merdeka" curriculum for the Natural Sciences (IPAS) subject in elementary schools. The research method used is qualitative descriptive with interview data collection techniques. The results of the research show six main discussions, including the meaning of character education, the urgency of character education, the meaning of IPAS learning with character education, and the relationship between the dimensions of the Pancasila Student Profile and character education.